Distribution of microbiota across different intestinal tract segments of a stranded dwarf minke whale, Balaenoptera acutorostrata. Issue 10 (12th August 2020) - Tian, Jiashen; Du, Jing; Lu, Zhichuang; Han, Jiabo; Wang, Zhen; Li, Duohui; Guan, Xiaoyan; Wang, Zhaohui
Abstract: Marine mammals are an important part of ocean ecosystems, of which, whales play a vital role in the marine food chain. In this study, the mucosa and contents from different intestinal tract segments (ITSs) of a stranded dwarf minke whale ( Balaenoptera acutorostrata ) were analyzed. The gut microbiota were sequenced using high‐throughput sequencing technology, based on a 16S rRNA approach. The microbial composition of the intestinal mucosa and its contents were similar in every single ITS. Large intestine microbiota richness and diversity were significantly higher when compared to the duodenum and jejunum. The dominant bacteria in the gut were Firmicutes and Actinobacteria ; the former was enriched in the large intestine, whereas the latter was more abundant in the duodenum and jejunum. Our findings provide novel insights for microbiota in B. acutorostrata . Abstract : This study has characterized the microbiota of five sampling sources (duodenum, jejunum, cecum, colon, and rectum) in a fresh stranded Balaenoptera acutorostrata carcass. Significant differences were observed in gut microbiota composition across different intestinal tract segments; the microbiomes of posterior compartments were more diverse than the foregut. The duodenum and jejunum were enriched for Erysipelotrichales, Selenomonadales, and Coriobacteriales, whereas Clostridiales were more abundant in the large intestine.